Planning For 5G: A Problem Structuring Approach for Survival in the Telecoms Industry. Issue 4 (3rd August 2016) - Jones, William; Sooriyabandara, Mahesh; Yearworth, Mike; Doufexi, Angela; Wilson, R. Eddie
ABSTRACT: This paper examines the application of systemic problem structuring methods to the development of a research strategy in response to the challenges of fifth generation (5G). The paper proposes a methodology for strategic decision making. The key stakeholders, objectives, technologies, and boundaries from existing literature are identified and problem structuring based on hierarchical process modeling is used to explore the dependency of certain features of 5G on specific technologies, giving an indication of the importance of certain technologies over others and thus insight into where to place research effort. The hard technical challenges of 5G are discussed and equally the importance of the soft social and business challenges explored. For context, we explain how 5G will provide a platform for innovations and discuss how new and existing businesses may use this to their advantage. Problem structuring is used to explore how the challenges and opportunities of future wireless systems are related to the process of developing new business models.